Chemical, Physical, and Hedonic Quality Characteristics of Fish Cereal from Toman Fish Albumin Extract (Channa micropeltes) as Functional Food - Evi Fitriyani; Nani Nuraenah (International Journal of Multi Discipline Science (IJ-MDS), 2023)
The nutritional value of fish cereal was determined by adding toman fish extract. Fish cereal is expected to be a useful food source rich in nutrients such as carbohydrates, vitamins, and minerals but rich in protein and albumin. Toman fish cereal is expected to be popular with people of all ages as a breakfast menu and can be a source of nutrition and increase endurance. The research aimed to obtain the formulation of toman fish albumin extract (Channa micropeltes) in fish cereal products as a functional food. This research was carried out in four stages: (1) preparation of fish albumin extract, (2) preparation of fish cereal; (3) Physical characteristics (hedonic test), fracture strength, and chemical characteristics (moisture content, ash content, protein content, fat content, and carbohydrate content), crude fibre content, albumin content, (4) determination of the best treatment using the Bayes method. The treatment with the addition of toman fish albumin consisted of 5 treatments with two replications. The treatment was carried out namely A1 0%, A2 30%, A3 35%, A4 40%, and A5 45%. The results showed that the highest protein content was around 4.57–13.33% and the albumin content of fish cereal was around 4.86–6.61%. This showed that fish cereal can be a functional food in increasing the immune system. Based on the Bayes test, the selected toman fish cereal formula was formula A2, namely 30% albumin extract.